PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN EARNINGS RESPONSE COEFFICIENT - Ariya Sapta Putra; Adelia Angelina; Muhammad Imran Syafe'ie; Nina Febriana Dosinta (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2023)
This study aimed to examine the effect of Corporate Social Responsibility (CSR) disclosure on the Earnings Response Coefficient (ERC). This study uses Bank Central Asia reporting and other supporting data for the 2012-2021. The results of this study found that CSR disclosure in the annual report and sustainability report of Bank Central Asia did not affect ERC. The results of this study imply that Bank Central Asia's CSR disclosure does not affect investors' investment decisions.